1985
DOI: 10.1111/j.1469-8749.1985.tb03802.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Predictions Compared With Present Vocational Status of 60 Young Adults With Cerebral Palsy

Abstract: SUMMARY A group of 97 cerebral‐palsied students between the ages of seven and 16 years were assessed in the 1960s and 1970s, and predictions were made as to their vocational status as adults. In 1983, 60 of the 76 over 18 years of age were contacted. 39 had been employed at some time since leaving high‐school, but only 17 were employed at the time of the survey. Of those who had worked, over half had achieved or exceeded their vocational predictions. Those in competitive employment were more likely to be mildl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, after a period of adjustment, the overall organization has proved to be good enough in most regions of Italy and integration is generally accepted by families with and without a member who has a disability. The important effects on the functional outcome of those with CP as a result of integration into mainstream schools has been stressed by other authors (O'Grady et al 1985).…”
Section: Educational Attainmentmentioning
confidence: 97%
See 2 more Smart Citations
“…However, after a period of adjustment, the overall organization has proved to be good enough in most regions of Italy and integration is generally accepted by families with and without a member who has a disability. The important effects on the functional outcome of those with CP as a result of integration into mainstream schools has been stressed by other authors (O'Grady et al 1985).…”
Section: Educational Attainmentmentioning
confidence: 97%
“…Different numbers concerning employment of people with CP are reported in the literature (Crothers and Paine 1959, Klapper and Birch 1966, Pollock and Stark 1969, Sillampaa et al 1982, O'Grady et al 1985, O'Grady et al 1995. Our numbers are generally lower (35% employed: about a half of these in sheltered employment and the other half competitively employed), but this discrepancy is likely to be related to several local factors, e.g.…”
Section: Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that young people with CP who were in school ranked getting a job as a top priority. However, for decades, adults with CP have continued to experience significantly lower rates in attaining and maintaining employment in comparison with their peers without disabilities . Furthermore, in the United States rates of employment for persons with CP have been cited to be considerably lower than employment rates of people living with other disabilities …”
mentioning
confidence: 99%